Finding Standard Levels for Some Special Physical Fitness Elements and Basic Skills of Volleyball for Juniors in the Middle Euphrates Clubs - Hussein, Ali Radhi Abdul; Hrebid, Nabeel Kadhim (Journal of Social Work and Science Education, 2024)
Since tests and measurements are thought of as the fundamental sports tests that reveal the true level that the player reaches, they shed light on the secrets of the ability so that the coach can know the true level of the players to achieve good results. This highlights the significance of the research by identifying standard levels for young volleyball players through specific physical fitness elements and basic skills using evaluation tools. Regarding the research problem, although there are several tests for the components of particular physical fitness and fundamental volleyball skills, the results only provide raw values that are meaningless to the coach. Therefore, in order to assess the components of unique physical fitness and fundamental skills, these raw scores need to be transformed into standard ratings. We can establish benchmarks and levels for junior volleyball players in the Middle Euphrates clubs by assessing their actual physical attributes and fundamental ball skills. The purpose of the study was to determine the degree of fundamental skills and unique physical fitness components among junior volleyball players in the Middle Euphrates clubs. Establishing benchmarks for assessments of particular physical fitness components and fundamental abilities for young volleyball players in the Middle Euphrates clubs. In order to address the nature of the study problem, we employed a descriptive technique that made use of the survey method as well as relationships and correlations. The research sample's highest percentage in the preparation, agility, and strength tests was at the standard level (good), according to the most significant findings. Additionally, the research sample's maximum percentage in the speed tests was at the standard level, or average. Additionally, the research sample's lowest percentage in the spiking test was at the standard level, which is quite poor.